2015
DOI: 10.3758/s13423-015-0966-5
|View full text |Cite
|
Sign up to set email alerts
|

The automaticity of perceiving animacy: Goal-directed motion in simple shapes influences visuomotor behavior even when task-irrelevant

Abstract: Visual processing recovers not only simple features, such as color and shape, but also seemingly higherlevel properties, such as animacy. Indeed, even abstract geometric shapes are readily perceived as intentional agents when they move in certain ways, and such percepts can dramatically influence behavior. In the wolfpack effect, for example, subjects maneuver a disc around a display in order to avoid several randomly moving darts. When the darts point toward the disc, subjects (falsely) perceive that the dart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 24 publications
5
28
0
Order By: Relevance
“…We suggest that the present data provide stronger evidence on the presence of the phenomenon. Our new method serves better the call from other researchers who suggested that by studying participants’ implicit interactive behaviour, more objective data can be obtained, thus it may be a more suitable way to test the perception of animacy [14,24,27]. In line with this, here we also investigated whether the observation of the dependent motion pattern performed by inanimate agents would have an effect on subjects’ behaviour.…”
Section: Discussionmentioning
confidence: 88%
“…We suggest that the present data provide stronger evidence on the presence of the phenomenon. Our new method serves better the call from other researchers who suggested that by studying participants’ implicit interactive behaviour, more objective data can be obtained, thus it may be a more suitable way to test the perception of animacy [14,24,27]. In line with this, here we also investigated whether the observation of the dependent motion pattern performed by inanimate agents would have an effect on subjects’ behaviour.…”
Section: Discussionmentioning
confidence: 88%
“…a particular class of movement), they fail to demonstrate that there is a perceptual presentation of psychological states. Thus, in contrast to the conclusion that participants perceive goal‐directedness (van Buren, Uddenberg and Scholl , 797), the worry is that the relevant perceptual state presents chasing, which then elicits the supplementary attribution to the chaser the desire catch its target, or the intention to flee. However, chasing is the superordinate visual classification of the moving shapes ‐ the overall category in which the perceptual experiences are grouped.…”
Section: A Change Of Strategymentioning
confidence: 83%
“…Furthermore, the attribution of animacy from these geometric shapes allows for inferences about goals, intentions, and personality characteristics and permits subsequent mechanisms of social cognition, such as mentalizing and empathy (Heider & Simmel, 1944; Santos et al, 2010; Scholl & Tremoulet, 2000). In normal people, these downstream social cognitive processes necessarily follow once animacy is perceived (van Buren et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms help detect goal-directed motion, attribute intention, distinguish intentional movements from mechanical ones, and dissociate intentionality from animacy detection (Blakemore et al, 2003; Gao, Scholl, & McCarthy, 2012; Lee, Gao, & McCarthy, 2014; Stosic, Brass, Van Hoeck, Ma, & Van Overwalle, 2014). From these investigations, and others, two basic aspects of social attribution emerge: that of ascribing animacy (van Buren, Uddenberg, & Scholl, 2016; Gao and Scholl, 2011; Santos et al, 2010; Schultz & Bülthoff, 2013), and that of ascribing agency (Gobbini et al, 2007; Osaka, Ikeda, & Osaka, 2012; Stosic et al, 2014). …”
Section: Introductionmentioning
confidence: 92%